Observed and expected overall mortality for acute myocardial infarction during the COVID-19 pandemic in Italy: an analysis of nationwide institutional databases - Leonardo De Luca; Francesco Grippo; Paola D’Errigo; Alessandra Burgio; Stefano Rosato; Barbara Giordani; Giorgia Duranti; Giovanni Baglio (Frontiers in Cardiovascular Medicine)
AimTo carry out a nationwide evaluation of both in- and out-of-hospital mortality for acute myocardial infarction (AMI) during the COVID-19 pandemic period in Italy.MethodsThis was a retrospective cohort study analysing overall mortality for AMI in Italy during the COVID-19 pandemic (March 1st, 2020–December 31st, 2021) and the previous 5 years (January 1st, 2015–February 29th, 2020). To carefully analyze both in- and out-of-hospital mortality for AMI (with or without concomitant COVID-19 infection) we used different institutional administrative sources of national data. Excess mortality related to AMI during the COVID-19 pandemic has been analyzed using the observed/expected ratio (OER).ResultsOver the 5 years pre-pandemic period, 150,299 fatal events related to AMI occurred. During the pandemic, the number of deaths related to AMI was 28,673 in 2020 and declined to 26,688 in 2021. The overall OER was 1.18 [95% confidence intervals (CI): 1.15–1.22] in 2020 and 1.19 (95% CI: 1.15–1.22) while out-of-hospital OER was 1.24 (95% CI: 1.20–1.29) in 2020 and 1.21 (95% CI: 1.16–1.25) during the pandemic. When excluding COVID-19 related deaths, the number of observed in-hospital deaths did not significantly differ from the expected both in 2020 and 2021 while the excess remains unchanged for out-of-hospital mortality.ConclusionsIn this analysis of nationwide institutional administrative databases, we documented an increase in observed mortality compared to the expected during the COVID-19 pandemic in Italy. This mortality increase is mainly attributable to out-of-hospital fatal events and related to concomitant COVID-19 infection for hospitalized AMI patients.